Transitioning to and thriving at the Olympic Training Center, Colorado Springs: phases of an adaptive transition - Diehl, R.; Poczwardowski, A.; Stambulova, N.; O'Neil, A.; Haberl, P. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
This study was focused on the process of an adaptive transition to the Olympic Training Center in Colorado Springs, CO (OTC) and guided by the research question: What were the dynamic transition experiences of elite resident-athletes that constituted their successful transition to the OTC? A retreatment of semi-structured interviews with six accomplished resident-athletes was conducted through the lens of the athletic career transition model to propose a temporally based Transition to the OTC (TOTC) empirical framework. The TOTC describes the successful transition as having four phases-preparation, assimilation, adaptation and thriving-involving the dynamic interactions between the resident-athletes and the OTC programs/staff influencing the perceived transition challenges, barriers, resources, coping strategies and outcomes throughout the four phases. Based on the TOTC, future research on the transitioning to residential training centres is outlined, and practical applications for the OTC staff, coaches and sport psychologists (e.g. developmentally relevant intake protocols, strengths-based interventions and orientation materials) are proposed: